Harnessing big data for precision medicine: radiomics based application of nanomaterials in MRI enhancement and multimodal therapy of hepatocellular carcinoma - Shen, Hongbin; Ran, Deshui; Zhu, Jida; Tao, Aoxiao; Zheng, Kai; Zhu, Qing; Wang, Haijun (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC) ranks among the most lethal malignancies worldwide, characterized by its high metastatic potential and poor prognosis. Early and precise detection and diagnosis of HCC remain a major clinical challenge. Magnetic resonance imaging (MRI), as the most widely used noninvasive technique for diagnosing liver diseases, currently suffers from limitations in traditional contrast agents, including low specificity and limited sensitivity, particularly when detecting small lesions. The emergence of nanotechnology offers novel approaches to enhance the diagnostic accuracy and therapeutic efficacy for HCC. Under the framework of big data driven precision medicine, this study explores the application of nanomaterials in HCC MRI enhancement and multimodal therapy. This review comprehensively summarizes two types of responsive nanomaterials: (1) Chiral Ni(OH)2 nanoparticles, which suggeste enhanced contrast in T1 weighted MRI and selective imaging capabilities for primary HCC and lung metastases; (2) β Lapachone loaded mesoporous MnO2 nanoparticles (HLMn), which effectively enhance the generation of reactive oxygen species (ROS) within tumor cells, disrupt redox homeostasis, and significantly improve the efficacy of chemo dynamic therapy (CDT). These nanoplatforms also exhibit potential to activate the c-GAS STING innate immune pathway, thereby augmenting antitumor immune responses. Nanomaterials hold great promise not only as enhanced contrast agents but also as precise therapeutic carriers. By integrating radiomics based imaging features with biological markers, we summarize current personalized HCC diagnosis and treatment planning models based on multimodal data. Simultaneously, we provide a critical summary of the synergistic application of advanced imaging and therapeutic nanotechnologies. In the future, leveraging big data for precise HCC diagnosis and treatment is anticipated to significantly improve patient survival.